The key to top-level endurance running performance: a unique example - Lucia, A.; Olivan, J.; Bravo, J.; Gonzalez-Freire, M.; Foster, C. (British Journal of Sports Medicine, 2008)
Successful athletes offer unique insight into the adaptation of human physiology to exercise. In this case report, running economy is hypothesised to represent the edge of a world class runner over his opponents. This variable has long been ignored, but was recently discussed in several articles as being a potential explanation for the difference in performance in endurance athletes despite similar other physiological measures such as VO2MAX or fractional oxygen utilisation.